2020
DOI: 10.1136/bmjopen-2020-037478
|View full text |Cite
|
Sign up to set email alerts
|

Strength of the association between Turner syndrome and coeliac disease: protocol for a systematic review and meta-analysis

Abstract: IntroductionCoeliac disease (CD) is a genetic autoimmune disorder characterised by a permanent sensitivity to the gluten contained in some grains. Certain patient groups are considered high risk for the development of CD, including, but not limited to, those with chromosomal disorders such as Turner syndrome (TS). Here, we present a protocol for a systematic review and meta-analysis that aims to comprehensively summarise the literature, and quantitatively estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This systematic review was conducted and reported following the 2009 Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines (35) (Supplementary Table 1). The review followed a previously published protocol (36) that was also registered in PROSPERO (registration number, CRD42019131881). The published protocol was designed to estimate the strength of association between TS and CD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This systematic review was conducted and reported following the 2009 Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines (35) (Supplementary Table 1). The review followed a previously published protocol (36) that was also registered in PROSPERO (registration number, CRD42019131881). The published protocol was designed to estimate the strength of association between TS and CD.…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive strategy was designed to search four electronic databases: PubMed, Scopus, Web of Science, and Embase. The search string was developed by an expert librarian (LÖ) and is available in the published protocol (36) and in Supplementary Box 1, which contains the results and search details for all databases. The literature search was performed in December 2019 with no restrictions on language or region.…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations